2015
DOI: 10.1097/bsd.0b013e31829046ca
|View full text |Cite
|
Sign up to set email alerts
|

Removing Outer Gloves as a Method to Reduce Spinal Surgery Infection

Abstract: This study shows that the removal of an outer pair of gloves before handling instrumentation may be a simple, cost-effective, and practical way to reduce the burden of postoperative infection following lumbar spinal fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…One recent study found that infection rates following posterior lumbar fusions decreased from 3.35% to 0.48% with removal of an outer pair of gloves before handling instrumentation. 26 Additionally, several studies have shown that prophylactic intraoperative application of powdered vancomycin in addition to preoperative intravenous cefazolin significantly decreased postoperative infection rates. 14,27 One study comparing 911 patients receiving preoperative cefazolin and 2 g vancomycin to 821 patients receiving only preoperative cefazolin found a decrease in infection rates from 2.6% in the control group to 0.2% in the treatment group (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…One recent study found that infection rates following posterior lumbar fusions decreased from 3.35% to 0.48% with removal of an outer pair of gloves before handling instrumentation. 26 Additionally, several studies have shown that prophylactic intraoperative application of powdered vancomycin in addition to preoperative intravenous cefazolin significantly decreased postoperative infection rates. 14,27 One study comparing 911 patients receiving preoperative cefazolin and 2 g vancomycin to 821 patients receiving only preoperative cefazolin found a decrease in infection rates from 2.6% in the control group to 0.2% in the treatment group (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…65 Rehman et al proposed a theory that after initial double gloving, with removal of the outer gloves prior to handling instrumentation, SSI rates might be reduced. 66 This study evaluated 179 patients undergoing lumbar spinal fusion with instrumentation using a posterior approach. A significant reduction in SSI was noted with removal of the surgeon's outer pair of gloves prior to handling instrumentation, compared to wearing the same pair of double gloves the entire time.…”
Section: Surgical Glovesmentioning
confidence: 99%
“…In addition, we included studies on glove change in hip and knee arthroplasty only. In a retrospective cohort study, Rehman et al . compared SSI rates before and after instituting a practice of removing outer gloves before handling implants during 389 lumbar spinal fusion cases.…”
Section: Discussionmentioning
confidence: 99%